Penyelesaian Sengketa di Luar Pengadilan sebagai Upaya Pemulihan Dampak Kerusakan Lingkungan - Vera Rimbawani Sushanty (Jurnal Ilmiah Penegakan Hukum, 2020)
This article aims to review the resolution of environmental disputes outside the court based on Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH). The problem is focused on efforts to protect and restore environmental damage. The method used in this research is normative or doctrinal legal research. Data is collected through a literature approach and analyzed qualitatively. The rapid development of the industry, requires natural resources in the form of raw materials and energy sources that are very large as well. The consequence of the industrial development process is the increase in waste produced by the industry. This is very possible for friction between the surrounding communities, which in turn can lead to conflict or dispute. This study concludes that resolving environmental disputes outside the court is considered more beneficial because if it takes a case in court it takes a long time. By shortening the process the impact of environmental damage can be more quickly addressed so that the ecosystem can soon recover and social, economic and cultural life can proceed as it should.